Late Calcific Mitral Stenosis After MitraClip Procedure in a Dialysis-Dependent Patient - Pope, Nicolas H. (Ann Thorac Surg, 2013)
The EVEREST II trial investigated the MitraClip (Abbott Vascular, Menlo Park, CA) in patients with severe mitral regurgitation (MR) undergoing surgical procedures. Although mitral stenosis was not reported in this cohort, this trial excluded patients receiving dialysis. We report a case of a 43-year-old HIV-positive, dialysis-dependent patient with nonischemic cardiomyopathy and severe MR, who was considered at high operative risk because of frailty. She was treated with a MitraClip as part of the REALISM high-risk registry. Her symptomatic MR improved but severe symptomatic mitral stenosis developed 28 months after the MitraClip procedure. At that point, she was felt to be a better operative candidate but required open mitral valve replacement. Pathologic examination demonstrated significant calcification of the leaflets around the MitraClip devices.